2007
DOI: 10.1073/pnas.0702228104
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclophilin D inactivation protects axons in experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis

Abstract: Multiple sclerosis (MS) is the leading cause of neurological disability in young adults, affecting some two million people worldwide. Traditionally, MS has been considered a chronic, inflammatory disorder of the central white matter in which ensuing demyelination results in physical disability [Frohman EM, Racke MK, Raine CS (2006) N Engl J Med 354:942–955]. More recently, MS has become increasingly viewed as a neurodegenerative disorder in which neuronal loss, axonal injury, and atrophy of the CNS lead to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
159
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(166 citation statements)
references
References 53 publications
6
159
0
1
Order By: Relevance
“…Recently, it was shown that when mice null for the cyclophilin D gene were induced with EAE, they recovered earlier than their wild-type counterparts (Forte et al, 2007). Although these null mice had similar inflammatory scores as wild-type controls, they had more spared axons, which were attributed to the neurons in cyclophilin D null mice being more resistant to the reactive oxygen and nitrogen species encountered in EAE (Forte et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that when mice null for the cyclophilin D gene were induced with EAE, they recovered earlier than their wild-type counterparts (Forte et al, 2007). Although these null mice had similar inflammatory scores as wild-type controls, they had more spared axons, which were attributed to the neurons in cyclophilin D null mice being more resistant to the reactive oxygen and nitrogen species encountered in EAE (Forte et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…More specific evidence for the involvement of mPT in neurological disorders has more recently been obtained with genetically modified mice lacking cyclophilin D, an important modulator of the mPT and the mitochondrial receptor for CsA. The knock-out mediated resistance to cerebral focal ischemia, experimental multiple sclerosis and as well cardiac ischemia [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Given the critical role of calcium accumulations in contused axons, it is important to consider where the intra-axonal calcium is coming from and which downstream mechanisms it initiates. In vitro and in a multitude of neurological conditions, including trauma, ischaemia, inflammation and degeneration 12,26 , a broad range of mechanisms have been implicated as sources for elevated axonal calcium, including extracellular sources (for example, voltage-gated ion channels [17][18][19] , the plasma membrane sodiumcalcium exchanger [20][21][22] , the acid sensing ion channel 27 or nodal glutamate receptors 23 ), as well as intracellular stores (such as mitochondria 28 or the endoplasmic reticulum 29 ). Our in vivo analysis now indicates that mechanoporation, that is, the formation of pores in the plasma membrane as first described after diffused brain injury 24 , is a dominant source of calcium influx at least in the first hours after contusion.…”
Section: Discussionmentioning
confidence: 99%